Arduino-Assisted Robotic and Coding Applications in Science Teaching: Bulb Brightness Activity - Nevin Kozcu Cakir; Sıla Yurdakul; Gürcan Çetin (Araştırma Temelli Etkinlik Dergisi, 2022)
This research aims to design a sample Arduino-assisted robotics and coding activity in accordance with the 5E instructional model. Also, it aims to set an example for how technology is integrated into science courses, especially in the structuring of abstract and hard-to-understand concepts in science teaching. The activity provides guidance to science teachers. The study was carried out with the participation of 6th graders in a public school in the academic year 2021-2022. The designed activity was carried out in the science laboratory with the participation of 15 secondary school students in the science course. The related activity was prepared for the concept of bulb brightness in the chapter on electricity in the secondary school 6th-grade science curriculum. This activity also aims at teaching students how to code, improving their attitudes and motivation towards the course, and helping them relate the factors that influence bulb brightness with real life.